Historical dictionary of romanticism in literature - Varner, Paul (Historical dictionaries of literature and the arts., 2014)
"The Historical Dictionary of Romanticism in Literature takes a close and comprehensive look at romanticism in literature through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 800 cross-referenced entries on the writers and the poems, novels, short stories and essays, plays and other works they produced; the leading trends, techniques, journals and literary circles, and the spirit of the times are also covered. This book is an excellent access point for students, researchers, and anyone wanting to know more romanticism in literature"--